LONGITUDINAL CHANGE OF RETINAL LAYER THICKNESS IN COGNITIVELY NORMAL ELDERLY SUBJECTS: Population-Based Cohort Study - Kim, Hyeong Min; Han, Ji Won; Kim, Ki Woong; Woo, Se Joon (Retina (Philadelphia, Pa.), 2024)
To identify longitudinal retinal layer thickness changes in normal eyes of cognitively healthy elderly people. Post hoc analysis was performed on 57 cognitively healthy elderly participants from the population-based Korean Longitudinal Study on Health and Aging and Korean Longitudinal Study on Cognitive Aging and Dementia cohort studies who underwent baseline and final optical coherence tomography scans. The peripapillary retinal nerve fiber layer, subfoveal choroid, and average retinal layer thickness at four quadrant (nasal, temporal, superior, and inferior) points 1 mm, 2 mm, and 3 mm from the center of the fovea were measured. The mean age of subjects was 75.1 years and the mean follow-up period was 55.9 months. Among the analyzed retinal layers, both the ganglion cell-inner plexiform layer and the outer nuclear layer at all 1 mm, 2 mm, and 3 mm points showed a statistically significant decrease in thickness at the final visit compared with baseline. The annual decrease rates were -1.2 µm/year at 1 mm (total -6.6%), -1.3 µm/year at 2 mm (total -8.4%), and -1.1 µm/year at 3 mm (total -9.7%) for ganglion cell-inner plexiform layer and -0.6 µm/year at 1 mm (total -4.2%), -0.5 µm/year at 2 mm (total -3.9%), and -0.4 µm/year at 3 mm (total -4.1%) for outer nuclear layer. Aging plays a significant role in the reduction of ganglion cell-inner plexiform layer and outer nuclear layer thicknesses in cognitively healthy elderly individuals.